2020
DOI: 10.1159/000506921
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Seasonal Variation of Ménière’s Disease: Data from a Population-Based Study

Abstract: Introduction: Ménière’s disease (MD) is a disease of the inner ear. In Asian countries, there is one previous epidemiologic study that used a retrospective survey of a specific district. Previous studies have demonstrated that weather variables are strongly associated with symptom aggravation in MD. However, no study has reported on seasonal variation of MD. Methods: We conducted a retrospective population-based study using the Korean national health insurance claims database (NHICD). In the present study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
0
26
0
4
Order By: Relevance
“…In a more recent study by Formeister et al within the United States (U.S.), based on a population-based survey from the 2008 National Health Interview Survey (NHIS), the prevalence of VM in adults was estimated to be 2.7% ( 3 ). This is higher than the estimated prevalence of benign paroxysmal positional vertigo (BPPV) of 1.6% and that of Meniere's disease (MD) (0.2–0.5%) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 69%
“…In a more recent study by Formeister et al within the United States (U.S.), based on a population-based survey from the 2008 National Health Interview Survey (NHIS), the prevalence of VM in adults was estimated to be 2.7% ( 3 ). This is higher than the estimated prevalence of benign paroxysmal positional vertigo (BPPV) of 1.6% and that of Meniere's disease (MD) (0.2–0.5%) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 69%
“…Ménière’s disease (MD) is a multifactorial disorder of the inner ear characterized by vertigo, tinnitus, and sensorineural hearing loss 1 . Due to changes in diet and an increase in the aging population, the incidence of MD has rapidly increased 2 , 3 . In recent population-based studies, the incidence of MD was 13–118 per 100,000 persons 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to changes in diet and an increase in the aging population, the incidence of MD has rapidly increased 2 , 3 . In recent population-based studies, the incidence of MD was 13–118 per 100,000 persons 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological factors, including ambient atmospheric pressure, relative humidity, and temperature range, were related to the risk of Meniere’s disease in this study. Two previous studies have also demonstrated the associations between meteorological factors of atmospheric pressure and humidity with the risk of Meniere’s disease 14 , 45 . The risk of Meniere’s disease attack was 1.30 times higher at an atmospheric pressure below 1013 hectopascals (95% CI 1.10–1.54) 14 .…”
Section: Discussionmentioning
confidence: 82%